2017
DOI: 10.17583/qre.2017.2583
|View full text |Cite
|
Sign up to set email alerts
|

‘Because Sometimes Your Failures Can Also Teach You Certain Skills’: Lecturer and Student Perceptions of Employability Skills at a Transnational University

Abstract: To cite this article: Paterson, R. (2017). 'Because sometimes your failures can also teach you certain skills': Lecturer and student perceptions of employability skills at a transnational university.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…Furthermore, employer and graduate said differently on employability skill (Mohamed and Noor, 2013;Erni, 2018). However, students and lecturers share similar perspectives on the importance of employability (Paterson, 2017). Employability skills required by employers are interpersonal relations, coping with emotions, self-awareness, and empathy (Al-Alawneh, 2014).…”
Section: Employability Skillsmentioning
confidence: 99%
“…Furthermore, employer and graduate said differently on employability skill (Mohamed and Noor, 2013;Erni, 2018). However, students and lecturers share similar perspectives on the importance of employability (Paterson, 2017). Employability skills required by employers are interpersonal relations, coping with emotions, self-awareness, and empathy (Al-Alawneh, 2014).…”
Section: Employability Skillsmentioning
confidence: 99%
“…Employability therefore does not depend on the acquisition of a single skill and/or knowledge set, but is rather a multilayered concept influenced by a variety of stakeholders, including the individual candidate and prospective employers, as well as the educational content, context and opportunities. Employability is multifaceted in that it may be internal (it involves the academic performance, ambitions and confidence of students) (Hooley, 2017;Harry, Chinyamurindi & Mjoli, 2018) and/or external (it involves institutional reputation, credibility and the demand in a field of study) (Paterson, 2017).…”
mentioning
confidence: 99%
“…Of these, the latter can only really be acquired in genuine work situations, while the generic skills can be developed through established pedagogies such as collaborative project work, case study analysis or a variety of assessment tasks. The role of HEIs is to not only ensure that graduates make the most of their formal learning environment, but also help students to develop the ability to describe the skills and achievements they have acquired (Paterson, 2017). This is best facilitated if teaching staff are aware of the importance that learning environments have in skills development, and if the staff have the necessary pedagogic skills themselves to effectively support the learning process.…”
Section: Employability and Evidenced Based Pedagogymentioning
confidence: 99%
“…Training national labour forces for the demands of industry, essentially a top-down implementation of HE curricula, has drawn a variety of responses from other stakeholders, but again, these studies have been mostly limited to Anglo-Saxon countries, as detailed in the previous sections. Studies that explore stakeholder perceptions of employability in globalsouth contexts are rare; research in a transnational Central Asian setting indicated that students were lacking in their ability to describe their own employability narratives, possibly impinging on their ability to move from education to work environments (Paterson, 2017). Koloba (2017), in a quantitative study of South African university students, maintains that while there is a strong link between perceived employability and the employability skills of students, enhanced employability is also largely determined by the state of the local labour market.…”
Section: The Limited Context Of Pedagogy For Employability Researchmentioning
confidence: 99%